Environmental effects on the cohesive laws of the composite bonded joints. (April 2022) - Abdel-Monsef, S.; Renart, J.; Carreras, L.; Maimí, P.; Turon, A.
Abstract: This paper investigates the effect of environmental conditions on the cohesive law of composite bonded joints under mode I and mode II loadings. An inverse method recently developed by the authors has been used to extract the cohesive stress-separation relation from the experimental load–displacement curve without considering a predefined shape of the cohesive law. Two types of adhesively composite bonded joints were tested at three different temperatures, −55 °C, room temperature and 80 °C and two ageing conditions (wet-aged and non-aged) for four years. The shape and parameters of the cohesive law have been compared among the different ageing and test temperature conditions. The shape of the cohesive law that best fits the experimental results has been identified depending on the loading mode, test temperature and environmental conditions. Graphical abstract: